2005
DOI: 10.1099/vir.0.81107-0
|View full text |Cite
|
Sign up to set email alerts
|

HcPro, a multifunctional protein encoded by a plant RNA virus, targets the 20S proteasome and affects its enzymic activities

Abstract: absen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
83
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 56 publications
0
83
2
Order By: Relevance
“…Interestingly, a countereffect has been uncovered by the finding that the multifunctional HcPro viral protein (Helper component Protein), a potent suppressor of RNA silencing, associates with different 20S proteasomal subunits and interferes with the RNase activity of the 20S proteasome (Ballut et al, 2005;Jin et al, 2007;Dielen et al, 2011). Moreover, Arabidopsis mutants knocked out for each of the two At-PAE genes encoding the a5 subunit of the 20S proteasome were more susceptible to infection by Lettuce mosaic potyvirus (Dielen et al, 2011).…”
Section: Viral E3 Ubiquitin Ligasesmentioning
confidence: 99%
“…Interestingly, a countereffect has been uncovered by the finding that the multifunctional HcPro viral protein (Helper component Protein), a potent suppressor of RNA silencing, associates with different 20S proteasomal subunits and interferes with the RNase activity of the 20S proteasome (Ballut et al, 2005;Jin et al, 2007;Dielen et al, 2011). Moreover, Arabidopsis mutants knocked out for each of the two At-PAE genes encoding the a5 subunit of the 20S proteasome were more susceptible to infection by Lettuce mosaic potyvirus (Dielen et al, 2011).…”
Section: Viral E3 Ubiquitin Ligasesmentioning
confidence: 99%
“…HC-Pro also participates in symptom development, genome replication, and virus movement (Maia et al, 1996;Syller, 2006), whereas these capacities should be derived from its ability to suppress RNA silencing (Kasschau and Carrington, 2001;Díaz-Pendón and Ding, 2008). Furthermore, HC-Pros from different viruses have been reported to interact with various host factors and affect their functions, such as the ubiquitin/26S proteasome system (Ballut et al, 2005), the chloroplast precursor of ferredoxin-5 (Cheng et al, 2008), and chloroplast protein 1-deoxy-D-xylulose-5-phosphate synthase (Li et al, 2015).…”
mentioning
confidence: 99%
“…The helper component protease (HcPro) of potato virus Y can interact with three Arabidopsis 20S proteasome subunits (39). Ballut et al found that lettuce mosaic virus HcPro could interact with the Arabidopsis thaliana ␣5 subunit of the 20S proteasome, and they suggested that HcPro may modulate its RNase activity, contributing to an antiviral response (40). Recently, it was found that the HcPro protein of papaya ringspot virus (PRSV) could inhibit the catalytic activity of the host proteasome and that the inhibition was achieved through interaction with the 20S proteasome subunit ␣1 (41).…”
mentioning
confidence: 99%